The International Pediatric Endosurgery Group Evidence-Based Guideline on Minimal Access Approaches to the Operative Management of Inguinal Hernia in Children - Davies, Dafydd A; Rideout, Drew A; Clarke, Simon A (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2020)
Minimally invasive surgery (MIS) for inguinal hernia repair (IHR) in children has been reported for more than two decades. The International Pediatric Endosurgery Group (IPEG) Evidence-Based Review Committee chose MIS IHR as the inaugural topic for review and presentation at the 2016 IPEG annual meeting. English language articles published between January 1, 2009, and December 31, 2015, were reviewed and included in this evidence-based review after searching PubMed, Cochrane Reviews, ClinicalTrials.gov, Google Scholar, and EMBASE. Level 1a and 1b evidence supports the recommendations that operative time for bilateral IHRs should be considered shorter and postoperative complications rates should be considered lower in MIS repair over open. Recurrence rates are similar between the two methods (level 1a and 1b evidence). No level 1 evidence exists to support one MIS technique over another or that operating on a detected contralateral patent processus vaginalis during laparoscopy makes any difference in long-term outcome to the patient. The advantages of lower postoperative complications and shorter operative times have been found in studies of surgeons experienced in MIS repair and differences were small. The evidence in this review supports that MIS repair is a safe, effective method of IHR with proper training and mentorship.